Pengaruh Latihan Menggunakan Penghalang Cone Terhadap Ketepatan Shooting Petanque - Wijayanti, Wijayanti; Wahyu Dirgantoro, Edwin; Rahmadi, Rahmadi (Jurnal Porkes, 2024)
The problem of this research is the lack of maximum ability in petanque shooting accuracy. This study aims to examine whether there is an effect on training using cone barriers on petanque shooting accuracy. The method used is experimental with a quantitative approach, pre-experiment design one group pretest-posttest design. The entire population was used as a sample, namely 8 students of the Physical Education Study Program (JPOK) FKIP ULM. Sampling using total sampling technique. The instrument uses a shooting game station test distance of 6, 7, 8 and 9 meters. Data collection techniques using pretest and posttest. Data analysis techniques using descriptive statistics, normality tests, homogeneity tests, and hypothesis testing SPSS 23. The results obtained from data analysis and hypothesis testing through the average value have a significant increase from 10.38 to 15.63. Based on the results of the hypothesis test, the sig. (2-tailed) of 0.000 < 0.05, it can be said that Ho is rejected and Hα is accepted. The results of the calculation of the descriptive statistical values of the pretest and posttest so it can be concluded that there is an influence of training using cone barriers on Physical Education Study Program Students (JPOK) FKIP ULM in increasing the accuracy of shooting petanque.